TRADISI NGUMBAI SABAH ULUN LAMPUNG SAIBATIN PEKON BIHA KABUPATEN PESISIR BARAT - Nina Indayana; Iskandar Syah; Maskun Maskun (FKIP UNIVERSITAS LAMPUNG, 2016)
This study aimed to determine the procedures of Sabah Ngumbai Ulun Lampung Saibatin Pekon Biha Kecamatan Pesisir Selatan Kabupaten Pesisir Barat. The method of used in this research was descriptive method with qualitative approach. The results showed that procedure of Ngumbai Sabah has three phases the preparation phase consisted of: deliberation societies in the mosque, the result of deliberation, slaughtering sacrificial animals. The implementation phase consisted of mosque public gatherings, events penayuhan/ praying, eating foods, distribution of cendana water. Closing stages consisted of: the public come to the location of paddy, plugging palm shoots, cendana water flush around the location of the fields.Penelitian bertujuan untuk mengetahui Tata Cara Ngumbai Sabah Ulun Lampung Saibatin Pekon Biha Kecamatan Pesisir Selatan Kabupaten Pesisir Barat. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa tata cara Ngumbai Sabah mempunyai 3 (tiga) tahap yaitu tahap persiapan terdiri dari: musyawarah masyarakat di masjid, hasil musyawarah, menyembelih hewan kurban. Tahap Pelaksanaan terdiri dari: kumpul masyarakat di masjid, acara penayuhan/pembacaan doa, menyantap hidangan, pembagian air cendana. Tahap penutupan terdiri dari: masyarakat menuju ke lokasi sawah, menancapkan pucuk aren, menyiram air cendana ke sekeliling sawah.Kata kunci: ngumbai sabah, tata cara, tradisi